Regulatory structures and challenges to developmental extractives: Some practical observations from Ghana - Toni Aubynn (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
At the heart of an effective extractive resource-based economic transformation and development is an effective regulatory framework that guides the promotion of investments into the sector, the procedure for responsible extraction, and the management of the utilization of such resources. Ghana's endowment with significant amount of ferrous and non-ferrous minerals, including gold, bauxite, manganese, diamonds, and iron ore, as well as hydrocarbons, is well known. The country has been mining gold for over a century, ranking second in production in Africa. The country has also undergone various regulatory transformations that have resulted in improvements in the mining sector in the country. Drawing largely on the case of Ghana, this paper seeks to share the experience of a regulator and offers some perspectives on the purpose, content, and challenges of the practical regulation of an extractives sector in a lower middle-income economy. The paper looks at both the design and content of a regulatory system in the mining sector of Ghana and throws light on the practical challenges (technical and political) of implementation. In light of the increasing allure of resource nationalism in current times, the paper also briefly explores the manner in which relationships are established and maintained by the regulatory bodies with both large multinational companies and small artisanal mining operations. It also offers a brief reflection on three key international standards and arrangements (the International Finance Corporation, the Extractive Industries Transparency Initiative, and the International Council on Minerals and Metals) to highlight their impact on domestic regulations. Conclusions are drawn to underscore the importance of effective and collaborative regulations in maximizing the transformative potential of resource extraction in less developed, resource-endowed countries.
Keywords: 330; development; extractives; regulatory; resource-based; transformation